Credit Risk Determinants in Sub-Saharan Africa Banking Systems - Jimoh, Zainab; Afolabi, Babatunde; Balogun, Adekunle Alexander; Weya-Ajayi, Funbi; Azeez, Fadheelat (Acta Universitatis Danubius. Œconomica, 2024)
This study investigated credit risk determinants in sub-Saharan Africa banking systems. The global financial crisis in 2008 to 2009 has caused banking crises. This study used time series data within a timeframe of 2016–2023, which included 22 banks in SSA. A dynamic panel data method was employed for estimation, utilizing techniques such as pooled-OLS, fixed effects, two-step difference, and system GMM estimation. The results of the estimations showed that the ratio of non-performing loans to total gross loans would decrease with an increase in the real GDP growth rate. The study found that a 1% rise in the real GDP growth rate results in a 0.13–0.23% point decrease in non-performing loans. However, it was discovered that the following factors significantly and favorably affect non-performing loans (NPLs): trade openness, volatility index - VIX as a proxy for global volatility, domestic credit given by banks to the private sector as a proportion of GDP, inflation rate, and the hypothetical variable responsible for the global financial crisis of 2008–2009.